Interpretation of endpoints in a network meta-analysis of new oral anticoagulants following total hip or total knee replacement surgery - Harenberg, Job; Marx, Svetlana; Dahl, Ola E.; Marder, Victor J.; Schulze, Astrid; Wehling, Martin; Weiss, Christel (Thrombosis and Haemostasis, 2012)
New oral anticoagulant (NOAC) regimens [dabigatran 150 mg (D150) and 220 mg (D220), rivaroxaban 10 mg (R20), and apixaban 2.5 mg bid (A5)] were effective and safe compared to enoxaparin for the prevention of venous thromboembolism (VTE) following elective total knee (TKR) or hip replacement (THR) surgery. First a cluster analysis was used to identify homogeneous studies for the trial programs of each NOAC. Second, only studies reporting VTE and VTE-related death, major bleeding, and mortality were included. The odds ratio (OR) and 95% confidence interval (CI) were calculated for each NOAC regimen versus the comparator. Third, these data were used for the indirect comparison between NOACs. Cluster analysis identified duration of treatment (10 ± 5 and 34 ± 5 days) as the only homogeneous parameter across all NOAC programs (p>0.05) except for A5 and VTE over 10 ± 5 days (analysis not performed). The results of the calculated OR and 95% CI of the four NOAC regimens over 10 ± 5 and 34 ± 5 days showed inferiority of D150 and D220 compared to R10 for VTE (p<0.01, p<0.001). Comparisons of major bleeding and mortality were not different for all indirect comparisons. Despite the lack of standard definitions for VTE and bleeding outcomes, cluster analysis seems to be an appropriate tool to identify homogeneity across trial programs and to perform an indirect comparison for NOACs for prevention of VTE following TKR and THR surgery.
Keywords: Apixaban; dabigatran; rivaroxaban; knee replacement; hip replacement; network meta-analysis